2000
DOI: 10.1093/carcin/21.5.423
|View full text |Cite
|
Sign up to set email alerts
|

Roles of JNK, p38 and ERK mitogen-activated protein kinases in the growth inhibition and apoptosis induced by cadmium

Abstract: Cadmium (Cd), a human carcinogen, can induce apoptosis in various cell types. Three major mitogen-activated protein kinases (MAPKs), c-JUN N-terminal kinase (JNK), p38 and extracellular signal-regulated kinase (ERK), have been shown to regulate apoptosis. In this study we explore the ability of Cd to activate JNK, p38 and ERK, including their effects on Cd-mediated growth inhibition and apoptosis in a human non-small cell lung carcinoma cell line, CL3. The kinase activity of JNK was induced dose-dependently by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 75 publications
9
116
1
Order By: Relevance
“…Several reports have shown that cadmium induces apoptosis in various tissues and cells, both in vivo and in vitro (Hamada et al, 1997). E.g., cadmium-induced apoptosis was reported in rat testes (Xu et al, 1996), mouse liver (Habeebu et al, 1998), rat lung epithelial cells (Hart et al, 1999), CL-3 human lung carcinoma cells (Chuang et al, 2000), HeLa human cervix carcinoma cells (Szuster-Ciesielska et al, 2000) and Rat-1 fibroblast cells (Kim et al, 2000). Copper, for its part, can induce an upregulation of apoptosis and related genes in zebrafish (Luzio et al, 2013) or induces the apoptotic cell death in the copepod Tigriopus japonicus (Rhee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that cadmium induces apoptosis in various tissues and cells, both in vivo and in vitro (Hamada et al, 1997). E.g., cadmium-induced apoptosis was reported in rat testes (Xu et al, 1996), mouse liver (Habeebu et al, 1998), rat lung epithelial cells (Hart et al, 1999), CL-3 human lung carcinoma cells (Chuang et al, 2000), HeLa human cervix carcinoma cells (Szuster-Ciesielska et al, 2000) and Rat-1 fibroblast cells (Kim et al, 2000). Copper, for its part, can induce an upregulation of apoptosis and related genes in zebrafish (Luzio et al, 2013) or induces the apoptotic cell death in the copepod Tigriopus japonicus (Rhee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Berra et al (64) demonstrated that inhibition of basal ERK activity is sufficient to trigger apoptosis and p38 activation with no changes in Jnk phosphorylation. Chuang et al (65) showed that CdCl 2 activated Jnk and p38 signaling with a concomitant decrease in ERK signaling. The stimulated Jnk and p38 pathways are known to regulate cell proliferation, invasion, survival, migration, growth arrest, and apoptosis (41, 20 -24).…”
Section: Discussionmentioning
confidence: 99%
“…The BCA protein assay kit (Pierce) was employed to determine protein concentrations using bovine serum albumin as a standard. Equal amounts of proteins from each set of experiments were subjected to Western blot analysis as described (31). Antibodies were stripped from polyvinylidene difluoride membranes using a solution containing 2% SDS, 62.5 mM Tris-HCl, pH 6.8, and 0.7% (w/w) ␤-mercaptoethanol at 50°C for 15 min before re-probing with another primary antibody.…”
Section: Methodsmentioning
confidence: 99%